From Multicultural Experiences to Teaching Practices: Insights from Pre-Service English Teachers in Indonesian ELT Contexts - Dewi Listia Apriliyanti; Pratiwi Retnaningdyah; Syafi'ul Anam (IKIP Widya Darma Surabaya, 2026)
Objective: This study explores the multicultural experiences, attitudes, and efficacy of pre-service English teachers (PSETs) along with their reflections on teaching practices. Method: The study employed the Multicultural Efficacy Scale survey and semi-structured interviews. 107 PSETs from nine public universities and five private universities in West Java, Indonesia, participated in the survey. Results: The study identified two key findings. Firstly, most PSETs acquired background knowledge and experiences related to diversity and multiculturalism mainly through media (M=2.99, SD=0.82), diverse classmates (M=2.96, SD=0.82), and social interactions (M=2.78, SD=0.81). 84 (78.5%) of them exhibited moderate attitudes, and 56 of them (52.34%) demonstrated moderate multicultural efficacy in the English language teaching context. Secondly, participation in student exchange programs significantly enhanced their awareness and understanding of multicultural contexts. Additionally, the findings indicated that participants with high multicultural efficacy successfully integrated Indonesian cultural elements into English Language Teaching. In contrast, those with moderate and low efficacy made cultural adjustments to bridge gaps but lacked pedagogical strategies for embedding cultural reflections into their instruction. Novelty: This study contributes to ELT and multicultural education research by examining pre-service English teachers’ multicultural experiences, attitudes, efficacy, and instructional practices in the Indonesian context. The findings highlight the role of media, social interactions, and intercultural experiences in shaping awareness of cultural diversity. While most participants demonstrated moderate multicultural attitudes and efficacy, variations were evident in their ability to implement culturally responsive teaching. The study underscores the need for stronger pedagogical support to translate multicultural awareness into meaningful classroom practices.